Airborne collision evaluation between drone and aircraft engine : effects of position and posture on damage of fan blades - Liu, Hu (2021)
The incident of unmanned aerial vehicles (UAVs) incursion into aerodrome often happens due to the popularity of drones among amateurs, and this may lead to a threat to the safety of commercial aircraft operation. Hence, it is essential to estimate the damage level of commercial aircraft caused by drone strikes. From the data analysis of bird strike accidents over the period 1990-2019, it is found that the engine part is more susceptible to be damaged by bird strikes compared to the other aircraft parts. In this paper, the damage of engine fan blades caused by the drone ingestion is simulated by using a drone (MAVIC Pro) impinging onto a typical business engine (CFM56-5B) with the aid of FEM (finite element method). It is demonstrated that the collision position and collision posture both would affect the damage level of engine fan blades significantly. More damage to fan blades can be detected for the 75% collision position, and the complex collision posture would lead to much larger damage on the engine fan blades. The results presented in this work can be used to guide the decision made on the drone incursion incidents over the aerodrome.